Edukasi TPS 3R Darul Aman dan Masyarakat dalam Optimasi Pembuatan Pupuk Kompos di Pondok Pesantren Darul Aman, Gombara, Makassar, Sulawesi Selatan - Abdul Malik, Fhahri Mubarak; Khairuddin, Khairuddin; Aksa, Rahmad; Awaluddin, Akbar; Hapiwaty, Saldi; Ismail , Ismail; Azwar, Muhammad; Pranata, Andriy (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Helping TPS 3R partners to solve the problem of managing waste into compost is efficient and effective. Methodology: carried out at TPS 3R Darul Aman, method of implementing innovation by increasing the quantity and quality of compost using EM4 (effective microorganism) to accelerate the decomposition of organic matter and the ability to provide nutrients for plants. Results: improvement in soil management into compost and compost quality. Community service has been carried out involving TPS3R Darul Aman partners by providing education on making compost. Limitations: No study covers all aspects. Authors are advised to explain research limitations, as well as further studies or future plans. Contribution: The agricultural sector in the use of compost and the lack of TPS3R employees makes the waste management process difficult.